PENGARUH PENERAPAN PBL BERBANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV - Alfadillah, Dinni; Kartono, Kartono; Ghasya, Dyoty Auliya Vilda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Problems in science and science learning often occur when we do not use appropriate learning models and media in presenting subjects because students have difficulty understanding, being interested and paying attention to the material being taught. Low student learning outcomes will be caused by this. To overcome these problems, appropriate implementation techniques and educational resources are needed. This research aims to determine the effect of using the audiovisual source problem based learning (PBL) paradigm on the science learning outcomes of class IV students at SDN 17 Pontianak Kota. This type of research uses a quasi-experimental methodology with a non-equivalent control group design. The research population was forty-eight grade IV students at SDN 17 Pontianak City. Sampling was carried out using purposive sampling technique. The experimental group used a PBL model supported by audio-visual media, while the control group used a PBL model supported by print media. The instrument used is a test with measurement data collection techniques. Examples of data analysis techniques include normality test, homogeneity test, hypothesis test (t test), and N-gain test. Hypothesis testing produces tcount = 8.156054, which means tcount ttable, ttable = 2.059539 for dk (25 + 23- 2 = 26), and the significance threshold Î± = 5%. Therefore, Ha accepted. This shows that the science and science learning outcomes of class IV students at SDN 17 Pontianak City are influenced by the PBL model assisted by audio-visual media.